Targeted Brain Rehabilitation: Development, Feasibility, and Usability of a Novel Virtual Reality System for Phantom Limb Pain Management and Amputee Rehabilitation - Serbin, Ryan P; Frix, James T; Bowmar, Ethan; Johnsen, Kyle; Siebert, Marcie; Ahn, Grace; Loeffler, Bryan J; Gaston, R Glenn (The Journal of hand surgery (American ed.), 2025)
Phantom limb pain (PLP), which affects up to 1.6 million amputees in the United States, is often inadequately controlled with current treatment strategies. Although surgical interventions like targeted muscle reinnervation and regenerative peripheral nerve interfaces can effectively address peripheral pain generators, the central mechanisms of PLP require complementary treatment approaches. This study introduces targeted brain rehabilitation (TBR), a novel virtual reality system designed to address the limitations of current therapies and provide a comprehensive, accessible solution for PLP management. Targeted brain rehabilitation incorporates a structured, four-phase approach aimed at gradually engaging the plasticity of cortical regions involved in phantom limb perception and pain. A two-phase study was conducted: (1) a survey of 36 upper-extremity amputees to inform the design of the TBR system, and (2) a single-session feasibility and usability study with 10 upper-extremity amputees. The TBR system incorporates four phases: laterality recognition, guided meditation, virtual mirror feedback, and guided motor execution, each targeting specific cortical regions and mechanisms implicated in PLP. The survey revealed that ease of use (77.8%) and decreased PLP (58.3%) were the most desired features and treatment outcomes, respectively. The TBR system demonstrated excellent usability (system usability scale: 87.8 ± 10.6), minimal simulator sickness (simulator sickness questionnaire: 0.7 ± 2.4), and considerable pain reduction (numeric pain rating scale decreased from 5.0 ± 2.0 to 2.0 ± 1.6). Participants identified the guided motor execution phase as most helpful for phantom limb position (60%), control (70%), and pain reduction (60%). Notably, 90% of participants reported changes in phantom limb position after a single-session. The TBR system shows promise as an engaging, accessible, and potentially effective treatment for PLP, addressing both somatosensory and kinesthetic symptoms. By leveraging principles of neuroplasticity and cortical reorganization, TBR offers a novel approach to PLP management. Therapeutic IV.